Peran Komitmen Organisasi dan Workplace Incivility terhadap Organizational Citizenship Behavior pada Staf RSU di Kebumen - Prameswari, Setya; Dwiyanti, Retno; Rahardjo, Pambudi (PSIMPHONI, 2022)
This study aims to evaluate the predictive power of organizational commitment and workplace incivility on organizational citizenship behavior among employees at Purbowangi General Hospital. Utilizing a quantitative approach with multiple regression analysis, this research involved 132 employees from the hospital. Data were collected using the Organizational Citizenship Behavior scale (26 items) adapted from Sharma and Jain (α = 0.969), the Organizational Commitment scale (16 items) adapted from Allen and Meyer (α = 0.693), and the Workplace Incivility scale (28 items) adapted from Martin and Hine (α = 0.942). Analysis results revealed an F-value of 83.597 (p < 0.001), indicating a significant positive effect of organizational commitment on organizational citizenship behavior. Conversely, an F-value of 171.919 (p < 0.001) showed a significant negative impact of workplace incivility on organizational citizenship behavior. Additionally, an F-value of 137.071 (p < 0.001) confirmed that both organizational commitment and workplace incivility significantly affect organizational citizenship behavior among employees at Purbowangi General Hospital. These findings underscore the importance of enhancing organizational commitment to promote positive organizational citizenship behaviors and reducing workplace incivility. Future research should consider longitudinal studies to assess how changes in organizational commitment and workplace incivility over time influence organizational citizenship behavior.